COMPONENTS OF THE TRAINING PROGRAM FOR EDUCATORS WORKING ON THE DEVELOPMENT OF THE MATHEMATICALLY GIFTED STUDENTS POTENTIAL - Natalia Bonchuk (International Journal of Innovative Technologies in Social Science, 2021)
The article is devoted to the formation and improvement of competencies of teachers and psychologists of secondary schools to identify and develop mathematically gifted students. It has been identified the components of the training program of basic competencies that psychologists and subject teachers must have to recognize and develop mathematical talent. The results of an empirical study of an educational project are online training for educators to deepen their theoretical knowledge of mathematical talent and the development of practical skills of organizing the educational process for students with a high level of ability in the field of exact sciences. It was found that training in the development of competencies is an effective way to improve the skills of teachers to understand the essence of talent, the peculiarities of its detection in students, prevention of loss of potential, development of individual educational trajectories, use of new learning technologies and ways to develop personal skills.